Succinate dehydrogenase mutations: paraganglioma imaging and at-risk population screening. Issue 3 (March 2019) - Cavenagh, T.; Patel, J.; Nakhla, N.; Elstob, A.; Ingram, M.; Barber, B.; Snape, K.; Bano, G.; Vlahos, I.
Abstract : Paragangliomas are rare vascular tumours of the autonomic nervous system. They can be classified as sympathetic or parasympathetic. Sympathetic paragangliomas, which include phaeochromocytomas, tend to be functional and symptomatic. Parasympathetic paragangliomas are usually non-functional and may present with mass effect. Forty percent of paragangliomas are linked to genetic syndromes, most commonly due to mutations of the succinate dehydrogenase (SDH) enzyme complex and are collectively known as paraganglioma syndromes, of which five are described. Genetic testing is recommended for all patients, and their first-degree relatives, diagnosed with paragangliomas. When SDH mutations are discovered, biochemical screening and imaging surveillance is indicated. There is currently no consensus on imaging surveillance protocols. Most advocate full-body imaging, but the choice of technique and frequency varies. If paragangliomas are demonstrated, functional imaging to look for synchronous tumours or metastases is indicated. 2-[ 18 F]-fluoro-2-deoxy-d -glucose ( 18 F-FDG) positron-emission tomography (PET)-computed tomography (CT) is the technique of choice for metastatic evaluation, but [ 123 I]-metaiodobenzylguanidine or [ 111 In]-DTPA-octreotide scintigraphy are also utilised. Current research into emerging positron-emitting radiolabelled somatostatin analogues have yielded promising results, which is likely to be reflected in future guidelines. As genetic testing becomes increasingly prevalent, the need to answer the remaining questions regarding surveillance imaging is paramount.